Laser-induced graphene flexible grid line electrode for photovoltaic cell and preparation method of laser-induced graphene flexible grid line electrode

Through the laser-induced graphene flexible gate wire electrode preparation method, the problem of complex and high cost of graphene electrode preparation process in existing photovoltaic cells is solved, and an efficient, low-cost, green and environmentally friendly electrode preparation is achieved, which is suitable for a variety of types of photovoltaic cells and flexible electronic fields.

CN119767846APending Publication Date: 2025-04-04HEBEI UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411901377.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing preparation methods for graphene electrodes of photovoltaic cells have complex processes, high costs, and environmental pollution, and it is difficult to achieve efficient preparation of large-area, customized, and various types of photovoltaic cell electrodes.

Method used

Using the laser-induced graphene (LIG) flexible gate wire electrode preparation method, the PI film was adhered to the glass substrate by hydrosol, the grid wire pattern was designed and ablated using a CO2 laser to obtain the LIG gate wire, and the LIG gate wire was then transferred to the PDMS film and aligned and cured on the photovoltaic panel.

Benefits of technology

It realizes the simple and efficient preparation of laser-induced graphene flexible gate wire electrodes, which are characterized by high performance, high precision, low cost, green and environmental protection, and can replace traditional silver electrodes and are suitable for a variety of types of photovoltaic cells and flexible electronic fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119767846A_ABST
    Figure CN119767846A_ABST
Patent Text Reader

Abstract

The invention discloses a laser-induced graphene flexible grid line electrode for a photovoltaic cell and a preparation method thereof, and the preparation method comprises the following steps: adhering a polyimide film to a glass substrate through hydrosol; designing a grid line, and ablating on the PI film by using a laser to obtain a laser-induced graphene grid line pattern; packaging an LIG grid line electrode pattern by using polydimethylsiloxane, and curing in a vacuum drying box; soaking in water, and dissolving the hydrosol to separate the glass substrate from the PI film; separating the cured PDMS from the PI film, and transferring an LIG grid line pattern to the surface of the PDMS film from the PI film; and placing the PDMS film on the surface of the photovoltaic cell, and enabling the LIG gate pattern to be in contact with a silicon substrate of the photovoltaic cell to obtain the photovoltaic cell panel with the LIG gate line electrode. The grid line electrode preparation method has the advantages of being low in cost, customizable, high in efficiency and environmentally friendly, a traditional metal electrode can be replaced, large-area and refined grid line electrode manufacturing is completed, and the grid line electrode preparation method can be widely applied to the fields of photovoltaic cells and flexible electronics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of photovoltaic cells and flexible electronic technology, and specifically relates to a laser-induced graphene flexible grid line electrode for photovoltaic cells and a preparation method. The laser-induced graphene grid line electrode obtained by the preparation method has high performance and process flexibility, can replace traditional silver electrodes in photovoltaic cells, and can also serve as an electrode function in chemical and physical batteries. Background Art

[0002] The storage capacity of traditional non-renewable energy sources such as oil, coal, and natural gas is limited. With the continuous development of human society, they are facing depletion in the near future. Therefore, solar photovoltaic cells, as a green, clean, sustainable, and renewable energy form, have received urgent attention from the global energy industry. At present, the electrodes used in silicon-based photovoltaic cells are mostly traditional precious metal materials such as gold and silver. They inevitably face the problems of pollution and high costs in the mining and refining process, which limits the large-scale promotion and application of solar photovoltaic cells.

[0003] Graphene is a two-dimensional atomic crystal composed of carbon atoms with a hexagonal honeycomb structure. It has high thermal conductivity, electrical conductivity and light transmittance that are superior to other conventional materials. Its semi-metallic properties enable it to form a stable Schottky connection when in contact with the silicon substrate of a photovoltaic cell, which is beneficial to improving the photoelectric conversion efficiency of silicon-graphene photovoltaic devices. It has great application potential in the fields of photovoltaic cells and flexible batteries.

[0004] CN111192937B discloses a method for making an ultra-thin transparent graphene gate electrode. The method uses a chemical vapor phase method to synthesize a triangular monolayer MoS 2 Nanosheets and graphene films are spin-coated with PMMA as samples, and electron beam exposure is used to obtain electrode patterns on the sample surface. Developers and fixers are used to remove denatured PMMA to expose the electrode patterns, and then Au metal electrodes and oxide insulating layers are deposited respectively to make top-gate field-effect transistors to complete the production of photovoltaic cells. This method uses transferred graphene as a transparent electrode to replace the traditional evaporated metal electrode, avoiding cracks in the insulating oxide layer caused by electron beam exposure or metal electrode deposition. The high transmittance of graphene allows top-gate field-effect transistors to be used in the optoelectronic field. However, the preparation process of this method is relatively complicated, and the process involves a variety of chemical materials, and the preparation efficiency and cost need to be optimized.

[0005] CN110335805A discloses a silicon wafer surface treatment method for in-situ growth of graphene. The method immerses the silicon wafer in a hydrofluoric acid solution and an alcohol solution of a phenol derivative successively to remove the natural oxide layer on the surface of the silicon wafer and expose the reactive sites for in-situ growth of graphene. The invention uses a phenol derivative on the surface of clean silicon to passivate the dangling bonds, which reduces the contact angle of the silicon wafer surface on the one hand and provides nucleation sites for the growth of graphene on the other hand, so that large-area graphene can be prepared in situ for the preparation of silicon-based graphene devices. However, this method requires the use of corrosive hazardous chemicals such as hydrofluoric acid, and nitrogen / inert gas is used in the drying process, which brings inconvenience to the preparation process.

[0006] The current method for preparing graphene electrodes for photovoltaic cells still has disadvantages such as high process requirements, complex processes, and large amounts of chemical materials. Therefore, it is necessary to explore and develop a more efficient, safer, and lower-cost method for preparing flexible grid line electrodes. Summary of the invention

[0007] Taking into account the above-mentioned deficiencies in the prior art, the technical problem to be solved by the present invention is to provide a simple and efficient method for preparing laser-induced graphene flexible grid line electrodes for photovoltaic cells, which is suitable for large-area, customized, and multi-type photovoltaic cell electrode preparation, and at the same time has the characteristics of high performance, high precision, low cost, and green environmental protection.

[0008] The technical solution adopted by the present invention to solve the technical problem is: A method for preparing a laser-induced graphene flexible grid line electrode for a photovoltaic cell comprises the following steps: Step 1: Use a hydrosol to adhere the PI film to a flat and smooth glass substrate, design a grid line pattern, import it into the laser supporting software, and then ablate the LIG grid lines on the PI film; Step 2, prepare PDMS solution, pour it on the surface of PI film to form a thin film, complete the encapsulation of LIG gate electrode, and put it in a vacuum drying oven for drying and curing; Step 3: Soak the PI film with LIG grid lines and the glass plate in water to dissolve the hydrosol, and the PI film falls off the glass plate. Peel off the PDMS film and the PI film, and the LIG grid lines are transferred from the PI film to the surface of the PDMS film;

[0009] Step 4: Place the PDMS film with LIG grid lines on the photovoltaic panel, align and contact the LIG grid lines with the exposed silicon substrate grid, apply uncured PDMS solution on the four sides of the panel to act as an adhesive between the PDMS film and the substrate, and place it in a vacuum drying oven for drying and curing.

[0010] Furthermore, the thickness of the PI film is 50-200 μm.

[0011] Furthermore, the laser in step 1 is CO 2 Laser, ultraviolet laser or femtosecond laser; the laser wavelength is 10.6 μm, 355 nm or 1053 nm, the output mode is grating mode when preparing LIG, the laser power is 4-10 W, the laser scanning speed is 50-130 mm / s, and the pixel density is 500-1000.

[0012] Furthermore, in step 1, the width of the LIG mesh grid lines produced is 100-300 μm.

[0013] Furthermore, in step 2, the mass ratio of PDMS polymer to crosslinker is 10:1, 9.5:1, 9:1, 8.5:1 or 8:1, the drying temperature is 80-120°C, the drying time is 0.5-2h, and the thickness of the cured PDMS film is 100μm-1mm.

[0014] Furthermore, in step 3, the immersion time is 5-10 min, and the peeling method of the PDMS film and the PI film is a 90° or 180° peeling method.

[0015] Furthermore, in step 4, the mass ratio of PDMS solution A:B is 10:1, 9.5:1, 9:1, 8.5:1 or 8:1, the drying temperature is 80-120° C., and the drying time is 0.5-2 h.

[0016] Furthermore, in step 4, the photovoltaic cell panel has a bare silicon substrate with a grid line electrode pattern for contact and bonding between the LIG grid line and the silicon substrate, and the portion other than the grid line is an anti-reflection coating.

[0017] Laser-induced graphene flexible grid electrode for photovoltaic cells. The LIG electrode pattern can be customized. The LIG grid line on the PDMS is flexible and can be bent, twisted or stretched. The PDMS film obtained by the above method has excellent light transmittance, which reduces the loss of light when passing through. Compared with the prior art, the present invention has the following beneficial effects: The preparation method and process of the laser-induced graphene flexible gridline electrode for photovoltaic cells of the present invention has the characteristics of simple preparation, low cost, customizability and green environmental protection. Compared with the traditional silver gridline electrode, LIG ​​technology significantly reduces the production cost, and the cost of a single electrode is reduced to less than 10 yuan, while avoiding the environmental pollution caused by the mining and extraction of metal materials. In addition, the laser processing technology brings high customization and flexibility, and the shape of the electrode pattern can be freely designed, and the graphic size range is 100μm-40cm. By adjusting the laser parameters, the width (100-300μm), thickness (50-200μm) and microstructure (porous, dense structure, or doped with other metal elements) of the gridline can be adjusted. This highly flexible process helps to customize the gridline design of photovoltaic cells, improve the conductivity of the electrode, reduce the shielding of light, and thus improve the photoelectric conversion efficiency. Finally, LIG ​​has good mechanical properties, and its own high flexibility and mechanical stability can withstand bending (bending radius <1mm) and deformation (0-40% stretching), showing great application potential in the field of flexible electronics.

[0018] The present invention proposes a high-performance, low-cost laser-induced graphene flexible grid electrode preparation method, which is expected to replace traditional electrode materials in a variety of photovoltaic cell fields, including flexible organic photovoltaic cells (replacing transparent indium tin oxide), flexible perovskite solar cells (replacing traditional precious metal electrodes Ag, Au), flexible silicon-based thin-film solar cells (replacing traditional metal grid lines), flexible dye-sensitized solar cells, flexible CIGS thin-film solar cells, flexible quantum dot solar cells, flexible cadmium telluride solar cells, etc. At the same time, it can also be used as a high-performance, flexible electrode in the fields of chemistry, physical batteries and flexible electronics.

[0019] Compared with the existing grid electrode preparation method, the method provided by the present invention expands the application types of photovoltaic cells, improves the mechanical and electrical properties of LIG electrodes, responds to the green environmental protection concept, and is conducive to the diversified development of photovoltaic cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The present invention is a schematic flow chart of a method for preparing a laser-induced graphene flexible grid line electrode for a photovoltaic cell.

[0021] Figure 2 This is a real-life plan view of the LIG grid lines transferred onto the PDMS membrane.

[0022] Figure 3 This is a three-dimensional picture of the actual state of LIG grid lines transferred onto the PDMS film.

[0023] Figure 4 Microscope image of LIG grid lines on PDMS film. DETAILED DESCRIPTION

[0024] The present invention provides an efficient and universal method for preparing a laser-induced graphene flexible grid electrode for photovoltaic cells. In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the scope of the present invention. Unless otherwise specified, the technical methods used are all common technical methods in this field.

[0025] like Figure 1-Figure 4 As shown, the present invention is a laser-induced graphene flexible grid line electrode for photovoltaic cells and a preparation method thereof. Figure 2 The physical plane unfolding diagram of the LIG grid lines transferred to the PDMS film, forming a large-area, high-precision grid-like grid electrode pattern. Figure 3 In the figure, the LIG grid lines are transferred to the PDMS membrane, which has good flexibility. Figure 4 Microscope image of LIG grid lines on PDMS membrane, magnification is 4x, scale bar is 400μm. It can be seen that after transfer, the LIG grid lines are firmly embedded in the PDMS membrane.

[0026] The steps of this method are: Step 1. Use hydrosol to adhere the PI film to a flat and smooth glass substrate. Use Auto CAD software to design the grid line pattern and import it into the laser software. Select a 1:1 graphic scale. The print interface size is the same as the laser workbench size to ensure the consistency of the pattern in the two software. Then place the PI film on the plane of the laser workbench. The workbench is a flat aluminum plate. Aluminum cannot absorb the laser wavelength and can ensure that the laser energy is fully applied to the object to be processed. The laser working environment is an atmospheric environment and no special inert gas needs to be injected. After setting the laser output mode, laser power, laser speed, PPI, Z-axis height and other parameters, start running. The carbon precursor contained in the PI film is converted into graphene under the photothermal effect of the laser to obtain LIG grid lines. LIG is a uniform three-dimensional porous structure, and its dense conductive network gives it good conductivity.

[0027] Step 2: Prepare PDMS solution with polymer and cross-linking agent in a certain mass ratio, and evenly pour it onto the surface of PI film to encapsulate LIG grid lines. Let it stand horizontally for 5-10 minutes to allow the solution to self-level, and at the same time, expel internal bubbles to obtain a uniform and smooth encapsulation layer film. Then put it in a vacuum drying oven, set the drying temperature to 80-120°C, and the drying time to 0.5-2h to completely cure the PDMS film. Too short a time or too low a temperature will result in insufficient curing, and subsequent PDMS film-related operations will easily produce holes and damage;

[0028] Step 3, put the PI-PDMS membrane with LIG grid lines and the glass plate into water. After 5-10 minutes, the hydrosol is fully dissolved and the PI-PDMS membrane can be easily peeled off from the glass plate. If the immersion time is too short, the hydrosol will not be fully dissolved. At this time, peeling off the membrane will cause unnecessary stretching or even tearing of the membrane. Use the 90° or 180° peeling method to separate the PDMS membrane and the PI membrane. During the separation process, keep the speed and force uniform to prevent damage to the PDMS membrane or the LIG grid lines. At this time, the LIG grid lines are gradually transferred from the PI membrane to the surface of the PDMS membrane;

[0029] Step 4: Prepare PDMS solution with polymer and cross-linking agent in a certain mass ratio, and apply it to the positions without anti-reflective coating on the four sides of the photovoltaic panel to act as an adhesive between the PDMS film and the panel. Place the PDMS film with LIG grid lines on the photovoltaic panel, align and contact the LIG grid lines with the exposed silicon substrate grid, and put it in a vacuum drying oven with a drying temperature of 80-120°C and a drying time of 0.5-2h for curing. Too short a time or too low a temperature will lead to insufficient curing and weak bonding.

[0030] In step 1, the thickness of the PI film is 50-200 μm, the laser output mode is the grating mode, the power is 4-10 W, the speed is 50-130 mm / s, the PPI is 500-1000, and the Z-axis height is the total thickness of the glass plate-hydrosol-PI film. This parameter range can produce a three-dimensional LIG with excellent structural consistency. The width of the LIG grid line produced is 100-300 μm.

[0031] In step 2, the mass ratio of liquid A:B is 10:1 (or 10:1, 9.5:1, 9:1, 8.5:1, 8:1. If the ratio of liquid A is too low, the flexibility of the PDMS film after curing will be reduced), the drying temperature is 80-120°C, the drying time is 0.5-2h, and the thickness of the cured PDMS film is 100μm-1mm.

[0032] In step 3, the immersion time in water is 5-10 min, and the peeling method of the PDMS film and the PI film is a 90° or 180° peeling method.

[0033] In step 4, a silicon channel with a grid pattern is left on the photovoltaic panel, and the rest is an anti-reflective coating. The mass ratio of A:B solution is 10:1 (or 10:1, 9.5:1, 9:1, 8.5:1, 8:1), the drying temperature is 80-120°C, and the drying time is 0.5-2h.

[0034] Preferably, the LIG grid lines on the PDMS have good mechanical properties, can be bent, folded, and stretched, can replace traditional metal electrodes, and have the potential to be applied to flexible photovoltaic cells. Flexible photovoltaic cells include but are not limited to one or more of flexible organic photovoltaic cells, flexible perovskite solar cells, flexible dye-sensitized solar cells, flexible CIGS thin-film solar cells, flexible silicon-based thin-film solar cells, flexible quantum dot solar cells, and flexible cadmium telluride solar cells.

[0035] The PDMS film obtained by the above method has excellent light transmittance (>95%), which reduces the loss of light when passing through.

[0036] Example 1 The method for preparing the laser-induced graphene flexible grid line electrode for photovoltaic cells in this embodiment has the following detailed steps: Step 1: Use hydrosol to adhere the PI film to a flat and smooth glass substrate, design a grid line pattern, and import it into the CO 2 In the laser, the LIG grid lines are then ablated on the PI film; Step 1 includes: taking a 200×200 mm square glass plate, wiping the surface dust with ethanol to prevent affecting the surface flatness of the subsequent PI film, sticking the water-soluble double-sided tape on the surface of the glass plate and tearing off the backing paper layer. Cutting a square PI film of the same size as the glass plate and 200 μm thick, wiping both sides clean, sticking it on the water-soluble double-sided tape, and using a scraper to remove the bubbles between the PI film and the hydrosol during the attachment process to ensure that the PI film and the hydrosol are flat and tightly bonded, which is conducive to the subsequent laser ablation of uniform and flat LIG grid lines on the surface of the PI film.

[0037] Subsequently, the grid-shaped grid electrode was drawn using Auto CAD software, which allows the drawing of electrode patterns of various sizes and shapes in a simple and convenient way. The CAD pattern was imported into the 10.6 μm wavelength CO 2 In the laser program, the film was placed on the laser workbench, the laser output mode was set to raster mode, the laser power was set to 4.5W, the laser scanning speed was set to 89mm / s, the pixel density was set to 500, and the Z-axis height was set to the total thickness of the glass plate-hydrosol-PI film: 3.2mm. After starting the laser, CO 2 The laser ablates a grid-like LIG pattern on the surface of the PI film. The LIG obtained with these parameters has a smooth surface, clear and neat edges, and a high degree of carbonization, making it very suitable as an electrode material. By adjusting the LIG parameters, the width (100-300μm), thickness (50-200μm), and internal microstructure (three-dimensional porous or dense structure) of LIG can be controlled, or it can be combined with other metal / organic materials to meet the photovoltaic cell applications with different electrode requirements.

[0038] Step 2. Mix liquid A and liquid B in the PDMS solution in a mass ratio of 10:1 to prepare a mixed solution with a total weight of 10.1g and stir it with a glass rod for 5 minutes. Pour the mixed solution on the surface of the PI film, let it stand horizontally for 5 minutes to make it self-leveling, and discharge some bubbles, and then put it in a vacuum drying oven. Set the drying temperature to 100℃ for 2h, and keep the vacuum state during drying. After drying, PDMS solidifies into a flat encapsulation layer on the surface of the PI film. The surface of the PDMS film is flat and smooth, the texture is transparent, the transmittance is above 95%, and the loss of light when passing through is small, which is beneficial to improve the photoelectric conversion efficiency of photovoltaic cells.

[0039] Step 3: Soak the PI film with LIG grid lines and the glass plate in water. After 10 minutes, the water-soluble double-sided adhesive dissolves, and the PI-PDMS film falls off the glass plate by itself. Use non-woven fabric to wipe the PI film dry. This peeling method relies on the dissolution of the hydrosol itself to lose its stickiness. When peeling, no additional stress will be generated on the PI-PDMS film, preventing the LIG grid lines from being torn, deformed or damaged. Use the 180° mechanical peeling method to gradually separate the PDMS film from the PI film. During this process, the speed and force must be uniform to prevent the PDMS film from tearing or the LIG grid lines from breaking. After the two are completely separated, the LIG grid lines originally formed by ablation on the surface of the PI film are completely transferred to the surface of the PDMS film. The LIG grid line electrode transferred on the PDMS film has excellent flexibility (bending radius <1mm) and good tensile properties (0-40% stretching), and can be used in the field of flexible photovoltaic cells and flexible electronics.

[0040] Step 4: A bare silicon substrate channel with the same grid line pattern as LIG has been reserved on the photovoltaic cell panel, and the part of the photovoltaic cell panel other than the grid line is an anti-reflective coating. Prepare PDMS solution, mix liquid A and liquid B in a mass ratio of 10:1, use a glass rod to stir for 5 minutes to mix them evenly, and then evenly pour the mixed solution on the positions around the photovoltaic cell panel without anti-reflective coating and grid lines as an adhesive between the PDMS film and the photovoltaic cell panel. Place the PDMS film with LIG grid lines on the cell panel, with the LIG layer facing down, and align and contact the grid lines with the exposed silicon channel, and the surrounding areas are initially bonded under the action of the uncured PDMS solution. Put the photovoltaic cell panel and the PDMS film in a vacuum drying oven, set the drying temperature to 100°C for 1h, and keep the vacuum state during drying. After drying, the PDMS film with LIG grid lines is tightly adhered to the photovoltaic cell layer to obtain a complete photovoltaic cell.

[0041] Comparative Example 1: A 100 μm thick PI film was pasted on a glass plate using a hydrosol and placed in a 10.6 μm wavelength CO 2Laser workbench. Set the laser output mode to grating mode, power to 1W, speed to 200mm / s, PPI to 500, and Z-axis height to the total thickness of glass plate-hydrosol-PI film 3.2mm. This laser parameter has low power and high scanning speed. The laser energy applied to the PI film is insufficient, and LIG with uniform carbonization and excellent quality cannot be produced. The resistance of the LIG line per centimeter is as high as MΩ level, which cannot be used as an electrode.

[0042] Comparative Example 2: A 100 μm thick PI film was pasted on a glass plate using a hydrosol and placed in a 10.6 μm wavelength CO 2 Laser workbench. Set the laser output mode to grating mode, power to 20W, speed to 10mm / s, PPI to 500, and Z-axis height to the total thickness of glass plate-hydrosol-PI film 3.2mm. This laser parameter has high power and low scanning speed, which applies too much laser energy to the PI film. The PI film is burned through, damaged, and curled due to excessive heat. The LIG is also broken by excessive energy, leaving a distorted, irregular, and discontinuous grating pattern on the PI film, which cannot be used as an electrode.

[0043] Comparative Example 3: Use the preferred laser parameters to make LIG grid lines on the PI film, and then prepare the PDMS solution. Mix liquid A and liquid B in a mass ratio of 5:1 and pour them on the surface of the PI film. Let it stand horizontally for 5 minutes to make it self-leveling, and expel some bubbles, and then put it in a vacuum drying oven. Set the drying temperature to 100°C for 1 hour, and maintain the vacuum state during the drying period. After the end, PDMS forms an encapsulation layer on the surface of the PI film. Compared with the PDMS film made with a ratio of 10:1, the reduction in the proportion of liquid A leads to a decrease in flexibility, and the maximum stretching rate can only reach about 20%. During the transfer process in step 3, LIG ​​broke.

[0044] In summary, the present invention provides an efficient and universal method for preparing laser-induced graphene flexible grid line electrodes for photovoltaic cells. The present invention has the advantages of high efficiency, reliability, environmental protection, low cost and customization. The obtained flexible LIG grid lines can replace traditional metal electrodes such as Ag and Au and be applied to photovoltaic cells, flexible electrodes, flexible electronic devices and other fields.

[0045] It should be understood that the above embodiments are only illustrations of specific implementation methods of the present invention, and are not intended to limit the scope of the present invention. For those skilled in the art, improvements or changes can be made based on the above descriptions, and all these changes and modifications should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A method for preparing a laser-induced graphene flexible grid electrode for a photovoltaic cell, characterized in that: The following steps are involved: Step 1: Use a hydrosol to adhere the PI film to a flat and smooth glass substrate, design a grid line pattern, import it into the laser supporting software, and then ablate the LIG grid lines on the PI film; Step 2, prepare PDMS solution, pour it onto the surface of PI film to form a thin film, complete the encapsulation of LIG gate electrode, and place it in a vacuum drying oven for drying and curing; Step 3, soaking the PI film with LIG grid lines and the glass plate in water to dissolve the hydrosol, the PI film falls off the glass plate, and the PDMS film and the PI film are peeled off. At this time, the LIG grid lines are transferred from the PI film to the surface of the PDMS film; Step 4: Place the PDMS film with LIG grid lines on the photovoltaic panel, align and contact the LIG grid lines with the exposed silicon substrate grid, apply uncured PDMS solution on the four sides of the panel to act as an adhesive between the PDMS film and the substrate, and place it in a vacuum drying oven for drying and curing.

2. The method for preparing a laser-induced graphene flexible grid line electrode for a photovoltaic cell according to claim 1, characterized in that: The thickness of the PI film is 50-200 μm.

3. The method for preparing a laser-induced graphene flexible grid line electrode for a photovoltaic cell according to claim 1, characterized in that: The laser in step 1 is a CO2 laser, an ultraviolet laser or a femtosecond laser; the laser wavelength is 10.6 μm, 355 nm or 1053 nm, the output mode is a grating mode when preparing LIG, the laser power is 4-10 W, the laser scanning speed is 50-130 mm / s, and the pixel density is 500-1000.

4. The method for preparing a laser-induced graphene flexible grid line electrode for a photovoltaic cell according to claim 1, characterized in that: In the step 1, the width of the LIG mesh grid lines produced is 100-300 μm.

5. The method for preparing a laser-induced graphene flexible grid line electrode for a photovoltaic cell according to claim 1, characterized in that: In the step 2, the mass ratio of PDMS polymer to cross-linking agent is 10:1, 9.5:1, 9:1, 8.5:1 or 8:1, the drying temperature is 80-120° C., the drying time is 0.5-2 h, and the thickness of the cured PDMS film is 100 μm-1 mm.

6. The method for preparing a laser-induced graphene flexible grid line electrode for a photovoltaic cell according to claim 1, characterized in that: In the step 3, the immersion time is 5-10 minutes, and the peeling method of the PDMS film and the PI film is a 90° or 180° peeling method.

7. The method for preparing a laser-induced graphene flexible grid line electrode for a photovoltaic cell according to claim 1, characterized in that: In step 4, the mass ratio of PDMS solution A:B is 10:1, 9.5:1, 9:1, 8.5:1 or 8:1, the drying temperature is 80-120° C., and the drying time is 0.5-2 h.

8. The method for preparing a laser-induced graphene flexible grid line electrode for a photovoltaic cell according to claim 1, characterized in that: In step 4, the photovoltaic cell panel has a bare silicon substrate with a grid line electrode pattern for contact and bonding between the LIG grid line and the silicon substrate, and the portion other than the grid line is an anti-reflection coating.

9. Laser-induced graphene flexible grid electrode for photovoltaic cells, characterized in that: The LIG electrode pattern can be customized, and the LIG grid lines on PDMS are flexible structures that can be bent, twisted or stretched.

10. The laser-induced graphene flexible grid electrode for photovoltaic cells according to claim 9, characterized in that: The PDMS membrane is obtained by the preparation method described in any one of claims 1 to 8.

Citation Information

Patent Citations

  • Silicon wafer surface treatment method for graphene in-situ growth

    CN110335805A

  • A method for fabricating ultrathin transparent graphene gate electrodes

    CN111192937B